Image, Fact and Faith - Selwyn, E. G. (New Testament studies, 1955)
This paper has been prompted by recent discussions of what is called ‘Demythologizing’. The movement which marches under that banner is important because its principal aim is to present Christianity to the modern mind in terms which will be more acceptable than those in which it has been traditionally clothed by Bible, Creed and Liturgy; and this is an aim which, whatever we may think of the method adopted for its pursuit, will be shared by all who have the Christian cause at heart. Those who believe the method to be mistaken are among the first to recognize the worth of the aim and feel all the more constrained in consequence to point to what they regard as a more excellent way.